Crafting and Testing an Elementary Device for Transporting U Ditches for Hands-on Learning in Road and Bridge Engineering at Technical High Schools - Putri, Mukhlisya Dewi Ratna; Mursid, Mursid (JURUSAN TEKNIK SIPIL, 2024)
This research aims to develop a simple and effective tool for moving U- shaped drainage channels (U ditch) with the aim of helping construction workers and farmers move U ditch more easily and efficiently. For this reason, this research takes the title